Developments of Diketopyrrolopyrrole‐Dye‐Based Organic Semiconductors for a Wide Range of Applications in Electronics. Issue 4 (3rd December 2019) - Liu, Qian; Bottle, Steven E.; Sonar, Prashant
Abstract: In recent times, fused aromatic diketopyrrolopyrrole (DPP)‐based functional semiconductors have attracted considerable attention in the developing field of organic electronics. Over the past few years, DPP‐based semiconductors have demonstrated remarkable improvements in the performance of both organic field‐effect transistor (OFET) and organic photovoltaic (OPV) devices due to the favorable features of the DPP unit, such as excellent planarity and better electron‐withdrawing ability. Driven by this success, DPP‐based materials are now being exploited in various other electronic devices including complementary circuits, memory devices, chemical sensors, photodetectors, perovskite solar cells, organic light‐emitting diodes, and more. Recent developments in the use of DPP‐based materials for a wide range of electronic devices are summarized, focusing on OFET, OPV, and newly developed devices with a discussion of device performance in terms of molecular engineering. Useful guidance for the design of future DPP‐based materials and the exploration of more advanced applications is provided. Abstract : Diketopyrrolopyrrole (DPP) is one of the most promising building blocks for the construction of semiconductors for organic electronics. Inspired by their success in organic field‐effect transistors and organic solar cells, DPP‐based semiconductors have been introduced into more devices. The DPP‐based semiconductors used for a wide range of electronic devices are summarized.